Biomimetic colloidal photonic crystals by coassembly of polystyrene nanoparticles and graphene quantum dots. Issue 61 (10th October 2018) - Huang, Dali; Zeng, Minxiang; Wang, Ling; Zhang, Lecheng; Cheng, Zhengdong
Abstract : We reported colloidal PCs with enhanced color visibility through the coassembly of modified graphene quantum dots into the close-packed array of polystyrene nanoparticles. Abstract : Biomimetic nanostructured materials with iridescent structural colors have attracted great attention due to their potential in photonic devices, materials science, and biomedical engineering. The technological applications of artificial photonic crystals (PCs), however, are often hindered by their low color visibility. Herein, we report colloidal PCs with enhanced color visibility through the coassembly of thioglycerol-modified graphene quantum dots (GQDs) into the close-packed array of polystyrene (PS) nanospheres. The enhanced polystyrene PCs were fabricated by both centrifugal sedimentation and drop-casting methods. The color visibility of the resulting PCs was found to be strongly dependent on the hydrothermal time ( i.e., carbonization) and the doping concentrations of GQDs. The PCs with brilliant reflection colors with red, green and blue (RGB) regions have been achieved by controlling the size of the constituent PS nanoparticles. As a proof of concept for photonic ink applications, we demonstrated a number of photonic images with RGB colors on multiple substrates including paper, silicon wafer and glass. This work is expected to provide new insight into the development of emerging advanced photonic crystals with high color visibility for applications such as colloidal paints, textile fabrics, and wearable displays.